Striatal dopamine influences the default mode network to affect shifting between object features - Dang, Linh C. (2012)
Cognitive flexibility, or the ability to change behavior in response to external cues, is conceptualized as two processes: one for shifting between perceptual features of objects and another for shifting between the abstract rules governing the selection of these objects. Object and rule shifts are believed to engage distinct anatomical structures and functional processes. Dopamine activity has been associated with cognitive flexibility, but patients with dopaminergic deficits are not impaired on all tasks assessing cognitive flexibility, suggesting that dopamine may have different roles in the shifting of objects and rules. The goals of this study were to identify brain regions supporting object and rule shifts and to examine the role of dopamine in modulating these two forms of cognitive flexibility. Sixteen young, healthy subjects underwent functional magnetic resonance imaging while performing a setshift task designed to differentiate shifting between object features from shifting between abstract task rules. Subjects also underwent positron emission tomography with 6-[(18)F]-fluoro-L-m-tyrosine (FMT), a radiotracer measuring dopamine synthesis capacity. Shifts of abstract rules were not associated with activation in any brain region, and FMT uptake did not correlate with rule shift performance. Shifting between object features deactivated the medial prefrontal cortex and the posterior cingulate and activated the lateral prefrontal cortex, posterior parietal areas, and the striatum. FMT signal in the striatum correlated negatively with object shift performance and deactivation in the medial prefrontal cortex, a component of the default mode network, suggesting that dopamine influences object shifts via modulation of activity in the default mode network.